2009
DOI: 10.1007/s12087-008-0034-9
|View full text |Cite
|
Sign up to set email alerts
|

Facets of Trust in Relationships – A Literature Synthesis of Highly Ranked Trust Articles

Abstract: This article offers a literature synthesis of 800 highly ranked trust articles published between 1966 and 2006. The literature synthesis is a tool for the development of a general trust model.The empirical findings support eight main clusters gained from forty identified key variables and three trust interaction types: trust between persons, trust between organizations, and trust between a person and an organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 60 publications
(36 reference statements)
0
17
0
2
Order By: Relevance
“…Several comprehensive reviews of the notion of trust revealed significant ambiguity and the multifaceted nature of the concept (Caldwell et al 2009;Ebert 2009;Fehr 2009;Gefen et al 2003b;McKnight and Chervany 2002;Wang and Emurian 2005). A common view is that of trust as a subjective belief that one party (the trustee) will behave in a manner which is in the interest of another party (the trustor) within a transaction (Dasgupta 1988;Gambetta 1988) such that 'there is a level of trust associated with a relationship' (Grandison and Sloman 2004).…”
Section: Defining Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Several comprehensive reviews of the notion of trust revealed significant ambiguity and the multifaceted nature of the concept (Caldwell et al 2009;Ebert 2009;Fehr 2009;Gefen et al 2003b;McKnight and Chervany 2002;Wang and Emurian 2005). A common view is that of trust as a subjective belief that one party (the trustee) will behave in a manner which is in the interest of another party (the trustor) within a transaction (Dasgupta 1988;Gambetta 1988) such that 'there is a level of trust associated with a relationship' (Grandison and Sloman 2004).…”
Section: Defining Trustmentioning
confidence: 99%
“…Based on a comprehensive literature review of 800 articles, Ebert (2009) classified online transactions into three categories: (1) between persons, i.e. inter-personal (P2P); (2) between organizations, i.e.…”
Section: Relationship-specific Attributesmentioning
confidence: 99%
“…Trust originates in personal relationship where it is often unconditional. In business, however, trust is usually conditional (Ebert, 2009), evolutionary (Vlaar et al, 2006), and even co-evolutionary (Yin and Zhao, 2008). Unconditional trust in business is only limited to 'safe zones' in shipping.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of trust is widely used in many different research disciplines, such as marketing, psychology, information systems and strategic management [14]. As a result, even within the IS discipline, numerous research approaches are taken to study trust and trust relationships [15]- [19].…”
Section: Trustmentioning
confidence: 99%